Systematic Literature Review of HCI Principles in Role – Playing Game Design: Towards a Comprehensive Framework for Enhancing Programming Skills - Panji Rachmat Setiawan; Maizatul Hayati Mohamad Yatim (SISTEMASI, 2026)
The absence of a comprehensive Human-Computer Interaction (HCI) framework specifically tailored for Role-Playing Games (RPGs) in programming skill development represents a critical research gap. This study conducts a systematic literature review (SLR) to synthesize interdisciplinary insights from game design, HCI, and cognitive psychology, aiming to establish foundational guidelines for integrating HCI principles into RPG design. Thirty peer-reviewed studies published between 2019 and 2025 were analyzed using the PRISMA approach. Findings reveal that embedding programming tasks into narrative-driven gameplay, supported by adaptive interfaces and motivational gamification, enhances learner engagement by approximately 35-50%, usability by 30-40%, and perceived effectiveness by 25-45%, depending on design strategies. Despite these promising outcomes, existing research remains fragmented, lacking a unified conceptual model linking usability, motivation, and technological innovation within RPG-based learning environments. This review identifies five key design dimensions usability heuristics, adaptive interaction, gamified motivation, narrative immersion, and personalization as essential to improving programming skill acquisition for novice users. Accordingly, the study proposes a preliminary structured framework to guide future RPG development that balances player experience with measurable learning outcomes. The novelty of this work lies in consolidating HCI principles into a systematic model for RPG-based programming learning, bridging the current gap between interaction design and educational functionality.